2022
DOI: 10.3389/fsurg.2022.929871
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Animal Models for Moyamoya Disease: A Species-Oriented Scoping Review

Abstract: Moyamoya disease (MMD) is a rare cerebrovascular disease characterized by progressive stenosis of large intracranial arteries and a hazy network of basal collaterals called moyamoya vessels. The etiology and pathogenesis of MMD are still obscure. The biggest obstacles in the basic research of MMD are difficulty in obtaining specimens and the lack of an animal model. It is necessary to use appropriate and rationally designed animal models for the correct evaluation. Several animal models and methods have been d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 106 publications
(120 reference statements)
0
1
0
Order By: Relevance
“…3,67,73 Autoimmune disorders, infections/inflammation, endothelial progenitor cells, and hemodynamic stress have been proposed as candidates for additional hits to trigger the onset of MMD. 3,67,73 Among these candidates, autoimmune disorders and infections/inflammation, namely, immune-related responses, are attracting increasing attention as a second hit to trigger disease onset with molecular and clinical evidence of their involvement in the onset of MMD. 74 As discussed above, studies on RNF213-deficient mice indicated the involvement of T-cell abnormalities in MMD.…”
Section: Consideration Of Causes and Triggers Of MMV Mmrsv And Rnf213...mentioning
confidence: 99%
“…3,67,73 Autoimmune disorders, infections/inflammation, endothelial progenitor cells, and hemodynamic stress have been proposed as candidates for additional hits to trigger the onset of MMD. 3,67,73 Among these candidates, autoimmune disorders and infections/inflammation, namely, immune-related responses, are attracting increasing attention as a second hit to trigger disease onset with molecular and clinical evidence of their involvement in the onset of MMD. 74 As discussed above, studies on RNF213-deficient mice indicated the involvement of T-cell abnormalities in MMD.…”
Section: Consideration Of Causes and Triggers Of MMV Mmrsv And Rnf213...mentioning
confidence: 99%